Current Flow Cytometric Assays for the Screening and Diagnosis of Primary HLH - Chiang, Samuel Cern Cher; Bleesing, Jack J.; Marsh, Rebecca A. (Frontiers in Immunology, 2019)
Advances in flow cytometry have led to greatly improved primary immunodeficiency (PID) diagnostics. This is due to the fact that patient blood cells in suspension do not require further processing for analysis by flow cytometry, and many PIDs lead to alterations in leukocyte numbers, phenotype, and function. A large portion of current PID assays can be classified as ‘phenotyping’ assays, where absolute numbers, frequencies, and markers are investigated using specific antibodies. Inherent drawbacks of antibody technology are the main limitation to this type of testing. On the other hand, ‘functional’ assays measure cellular responses to certain stimuli. While these latter assays are powerful tools that can be used to detect defects in entire pathways and distinguish variants of significance, it requires samples with robust viability and also skilled processing. In this review, we concentrate on hemophagocytic lymphohistiocytosis (HLH), describing the principles and accuracies of flow cytometric assays that have been proven to assist in the screening diagnosis of primary HLH.